Content-Based Language Teaching (CBLT) in ESP Courses in Indonesian Higher Education: A case study - Muliati Muliati; Syarifuddin Dollah; Sultan Baa (Indonesian TESOL Journal, 2022)
This study explores the implementation of CBLT in ESP courses within Indonesian higher education. It identifies categories of assessment within that implementation through a variety of classroom activities. The study looks at learning outcomes in which CBLT makes an impact on ESP learning, at types of teaching preparation, at teaching materials, and at various teaching methods employed in CBLT implementation. This research applies a case study research design, focused on Indonesian higher education, specifically Bosowa University, Makassar. Seven lecturers and ten students from the university’s non-English department were selected as participants in the study. They were selected purposively, as they had implemented CBLT in ESP courses in their classes. The instruments of data collection were documentation, observation, and interview. The findings of the study show that by implementing CBLT, the lecturers believed that they could teach the ESP courses more effectively. In addition, lecturers were able to manage and organise content material in their ESP teaching. Students enhanced their knowledge of specific English, as well as their communicative competence in real life, elevating the vocabulary pertaining to their disciplines. Finally, students believe that CBLT offers many opportunities for meaningful and purposeful language use. Detailed findings are presented here, and their implications discussed.